N-Methyl-D-Aspartate Receptors in Hematopoietic Cells: What Have We Learned? - Kalev-Zylinska, Maggie L.; Hearn, James I.; Makhro, Asya; Bogdanova, Anna (Frontiers in Physiology, 2020)
The N-methyl-D-aspartate receptor (NMDAR) provides a pathway for glutamate-mediated intercellular communication, best known for its role in the brain but with multiple examples of functionality in non-neuronal cells. Data previously published by others and us provided ex vivo evidence that NMDARs regulate platelet and red blood cell (RBC) production. Here, we summarise what is known about these haematopoietic roles of the NMDAR. Types of NMDAR subunits expressed in megakaryocytes (platelet precursors) and erythroid cells are more commonly found in the developing rather than adult brain, suggesting trophic functions. Nevertheless, similar to their neuronal counterparts, haematopoietic NMDARs function as ion channels, and are permeable to calcium ions (Ca2+). Inhibitors that block open NMDAR (memantine and MK-801) interfere with megakaryocytic maturation and proplatelet formation in primary culture. The effect on proplatelet formation appears to involve Ca2+ influx-dependent regulation of the cytoskeletal remodelling. In contrast to normal megakaryocytes, NMDAR effects in leukaemic Meg-01 cells are diverted away from differentiation to increase proliferation. NMDAR hypofunction triggers differentiation of Meg-01 cells with the bias towards erythropoiesis. The underlying mechanism involves changes in the intracellular Ca2+ homeostasis, cell stress pathways, and haematopoietic transcription factors that upon NMDAR inhibition shift from the predominance of megakaryocytic towards erythroid regulators. This ability of NMDAR to balance both megakaryocytic and erythroid cell fates suggests receptor involvement at the level of a bipotential megakaryocytic-erythroid progenitor. In human erythroid precursors and circulating RBCs, NMDAR regulates intracellular Ca2+ homeostasis. NMDAR activity supports survival of early proerythroblasts, and in mature RBCs NMDARs impact cellular hydration state, haemoglobin oxygen affinity and nitric oxide synthase activity. Overexcitation of NMDAR in mature RBCs leads to Ca2+ overload, K+ loss, RBC dehydration and oxidative stress, which may contribute to the pathogenesis of sickle cell disease. In summary, there is growing evidence that glutamate-NMDAR signalling regulates megakaryocytic and erythroid cells at different stages of maturation, with some intriguing differences emerging in NMDAR expression and function between normal and diseased cells. NMDAR signalling may provide new therapeutic opportunities in haematological disease, but in vivo applicability needs to be confirmed.